FLI1 Induces Megakaryopoiesis Gene Expression Through WAS/WIP-Dependent and Independent Mechanisms; Implications for Wiskott-Aldrich Syndrome - Wang, Chunlin; Sample, Klarke M.; Gajendran, Babu; Kapranov, Philipp; Liu, Wuling; Hu, Anling; Zacksenhaus, Eldad; Li, Yanmei; Hao, Xiaojiang; Ben-David, Yaacov (Frontiers in Immunology, 2021)
Wiskott-Aldrich Syndrome, WAS/WAVE, is a rare, X-linked immune-deficiency disease caused by mutations in the WAS gene, which together with its homolog, N-WASP, regulates actin cytoskeleton remodelling and cell motility. WAS patients suffer from microthrombocytopenia, characterized by a diminished number and size of platelets, though the underlying mechanism is not fully understood. Here, we identified FLI1 as a direct transcriptional regulator of WAS and its binding partner WIP. Depletion of either WAS or WIP in human erythroleukemic cells accelerated cell proliferation, suggesting tumor suppressor function of both genes in leukemia. Depletion of WAS/WIP also led to a significant reduction in the percentage of CD41 and CD61 positive cells, which mark committed megakaryocytes. RNAseq analysis revealed common changes in megakaryocytic gene expression following FLI1 or WASP knockdown. However, in contrast to FLI1, WASP depletion did not alter expression of late-stage platelet-inducing genes. N-WASP was not regulated by FLI1, yet its silencing also reduced the percentage of CD41+ and CD61+ megakaryocytes. Moreover, combined knockdown of WASP and N-WASP further suppressed megakaryocyte differentiation, indicating a major cooperation of these related genes in controlling megakaryocytic cell fate. However, unlike WASP/WIP, N-WASP loss suppressed leukemic cell proliferation. WASP, WIP and N-WASP depletion led to induction of FLI1 expression, mediated by GATA1, and this may mitigate the severity of platelet deficiency in WAS patients. Together, these results uncover a crucial role for FLI1 in megakaryocyte differentiation, implicating this transcription factor in regulating microthrombocytopenia associated with Wiskott-Aldrich syndrome.